HOW WILLIAM SHAKESPEARE CHANGED ENGLISH LITERATURE FOREVER - Ruzmetova Zilola Dilmurod kizi, (TADQIQOTLAR, 2026)
Abstract. The article examines the long-term influence of William Shakespeare on English literature, focusing on his transformation of dramatic form, poetic language, characterization, genre, and cultural imagination. Shakespeare did not merely enrich English literature with famous plays and sonnets; he expanded the expressive capacity of the English language, deepened the psychological structure of literary characters, and  created  models  of  tragedy,  comedy,  history,  romance,  and  poetic  drama  that continued to shape later writers.